Strategic International Management - Morschett, Dirk; Schramm-Klein, Hanna; Zentes, Joachim (Springer, 2015)
In this third edition, all chapters have been updated, new chapters integrated, all case studies revised and recent data were integrated. The concept, as it is described below, remained unchanged. Over the last few decades, international activities of companies have gained dramatically in importance. Empirical evidence for this statement can be found, for instance, in the rapid growth of world trade and in foreign direct investment flows as well as in the high share of intra-company trade on total world trade, indicating the relevance of cross-border value creation processes. Courses on International Management have, thus, become an integral part of most management studies at universities today and dedicated Masters and MBA programmes on International Management have emerged in recent years.